(untitled) (Amsterdam, 2016)
Contents: 1. Groundwater as an environmental issue in Asian cities 2. DPSIR framework for evaluating groundwater environment 3. Water environment in South Asia: an introduction 4. Groundwater environment in Chitwan, Nepal 5. Groundwater environment in Delhi, India 6. Groundwater environment in Hydarabad, India 7. Groundwater environment in Khulna, Bangladesh 8. Groundwater environment in Lahore, Pakistan 9. Water environment in Southeast Asia: an introduction 10. Groundwater environment in Bandung, Indonesia 11. Groundwater environment in Bangkok, Thailand 12. Groundwater environment in Dili, East Timor 13. Groundwater environment in Ho Chi Minh, Vietnam 14. Groundwater environment in Yangon, Myanmar 15. Water environment in Central and East Asia: an introduction 16. Groundwater environment in Beijing China 17. Groundwater environment in Bishkek, Kyrgyzstan 18. Groundwater environment in Seoul, South Korea 19. Groundwater environment in Tokyo, Japan
Keywords: Nước ngầm,Groundwater; Châu Á,Asia